Mixed Matrix Membrane Incorporating of MgAl-CO3 Layered-Double-Hydroxide for Enhanced Carbon Dioxide Separation - N. Fajrina; N. Yusof; A.F. Ismail; J. Jaafar; F. Aziz; W.N.W. Salleh; Noor Maizura Ismail (2021)
In this study, mixed matrix membranes were fabricated by incorporating MgAl-CO3 layered double hydroxides (LDH) into polysulfone (PSF) coated with low-cost commercial PEBAX polymer for enhancing CO₂/CH₄ separation. LDH was synthesized via a simple co-precipitation method and flat sheet membranes were fabricated by dry/wet inversion phase. The gas separation performance on pure PSF and LDH/PSF membranes were investigated. The physical property, chemical structure and membrane morphology were characterized by XRD, FTIR, and SEM. The sample membranes were tested with CO₂ and CH₄ gas for permeance performance and selectivity of CO₂/CH₄ was calculated. By incorporation of LDH, the CO₂ permeance increased about 54.6%. LDH mixed matrix membranes displayed the 18.2 GPU of CO₂ permeance and CO₂/CH₄ selectivity of 18.0. The LDH based membrane produces innovation in membrane technology by improving its morphology and permeance performance with great potential for large-scale CO₂ capture and separation.